Extract‐stent‐replace for treatment of upper baffle stenosis with pacing leads after atrial switch procedures for transposition of the great arteries: An approach to avoid "jailing" the lead. (18th August 2020) - Merrill, Miranda; Krebsbach, Angela; Przybylowicz, Ryle; Broberg, Craig S.; Burch, Grant; Henrikson, Charles A.
Abstract: Introduction: Venous stenosis is a late complication of the atrial switch (Mustard/Senning) procedure seen in patients with transposition of the great arteries ( d ‐TGA). Many atrial switch patients require cardiac implantable electronic devices (CIEDs) which further increases the incidence of venous stenosis. Stenosis of the superior limb of the systemic venous pathway (SLSVP) in the presence of CIED leads presents a management challenge. We propose a method for navigating SLSVP stenosis in atrial switch patients with CIEDs. Methods: The pulse generator and leads were removed using standard extraction techniques. Axillary access was retained via existing leads or new access was obtained. The interventional cardiology team, via groin access, performed stent‐angioplasty of the stenotic SLSVP. After stent deployment, the axillary access wire was snared from below, guided through the stent, and pulled into a long groin sheath. A sheath was then advanced over the axillary wire and into the groin sheath creating a path for passage of leads through the stent. New leads were advanced through the axillary sheath into the heart. Leads were secured using standard techniques. Results: All patients had a history of d ‐TGA and prior atrial switch procedures. In each case, there was stenosis of the SLSVP in the setting of a CIED lead. There were no immediate complications and there was no restenosis on follow‐up. Conclusion: Post‐atrial switch patients with CIEDs can develop stenosis of the SLSVP. A collaboration between electrophysiology and interventional cardiology can allow for device extraction, stent‐angioplasty, and lead reimplantation to avoid "jailing" the leads.